The Semiotic Analysis Meaning Of Love In Last Night On Earth BY Green Day - Livia Wulandari; Lina Fadiyah; Suhartawan Budianto; Rommel Pasopasti (PT Naureen Digital Education, 2023)
In song lyrics, the authors are free to express their imagination to make a representation of life. Each lyric contains its own meaning according to the creativity of the songwriters; many songs were created because of their personal experience with the loved ones. This research examines the meaning of love in the lyrics of Green Day's song Last Night on Earth using the semiotic theory of Roland Barthes. In this semiotic analysis, Roland Barthes exposes meanings of denotation, connotation, and myth regarding the meaning of love contained in the theme of the song. By using qualitative method, denotative meaning of the song is the power of love even though the distance separates the two. The connotative meaning relates to how the writer wrote a message to his wife to keep his love. The myth is correlated in when the songwriter loses everything he has because it was engulfed in flames, but he will stop at nothing to send his love to his wife. In conclusion, Green Day proves that there is still true love in him for the man’s wife despite any distance and bad condition.